Problem Based Learning (PBL) in Teaching English for Students of Primary School Teacher Education Department - Muhamad Sofian Hadi; Lidiyatul Izzah (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2018)
One of the learning models that can be implemented in increasing the students ability in English language is using Problem Based Learning (PBL). Problem Based Learning is a learning model that focuses on giving the solution for students in learning process. PBL provides the chance for students to find their problem and also creating the alternative solution to deal with their problems in English language learning. The aims of this study, by using PBL can increase the students’ ability in mastering English language. The participant of this study chosen from primary school teacher education department (PGSD) faculty of educational sciences, Muhammadiyah University of Jakarta. There several consideration in choosing the department as the object of this study. First, the student of this department lack of interest in joining the English subject, the learning process becomes ineffective. Second, as the future candidate of teacher for elementary school students, they need to concern with the ability of English language. Third, the average ability of students in mastering English is weak. The method used for this study based on qualitative/interpretive paradigm. This method concern on viewing the focus and problems of this study in a comprehensive way. The finding, based on the result of the study it can be shown that the students ability in English language increased as the researcher targeted from the beginning. And the learning process becomes more active after the use of Problem Based Learning. So, it can be concluded that the use of Problem Based Learning (PBL) can increase the students’ ability in mastering English Language.